Surgical Management of the Peripheral Osteoma of the Zygomatic Arch: A Case Report and Literature Review - Umberto Autorino; Claudia Borbon; Maria Chiara Malandrino; Giovanni Gerbino; Fabio Roccia (Case Reports in Surgery)
An osteoma is a benign, slow-growing, osteogenic neoplasm with a low recurrence rate that is typically characterized by the proliferation of a compact or cancellous bone. It can be peripheral, central, or extraskeletal. Usually asymptomatic, peripheral osteomas in the maxillofacial region commonly arise in the paranasal sinuses and mandible and rarely occur in the zygomatic arch, with only six previously documented cases in the literature. Here, we present the management of a solitary peripheral osteoma of the right zygomatic arch in a 72-year-old woman and a review of the literature.